Online information: theorising pedagogical attunements through technofeminist perspectives - Mary F. Rice; JuliAnna Ávila (Digital Culture & Education)
The purpose of this article is to conceptualise the teaching of online information evaluation through a technofeminist lens. This lens draws on work on entangled relationality in intra-activity, interconnectedness, materialities, and agencies while questioning the human/non-human binary. We provide a rationale for setting a research agenda about teaching online information literacies as spaces where technologies and literacies represent indistinguishable fluid ecologies. To achieve our goal of positioning the technofeminist perspective on the practice, research, and policy landscapes of online information evaluation, we focus on three broad perspectival attunements in thinking about online information evaluation as a concept. To illustrate these shifts, we draw on a curricular unit where preservice teachers are asked to interrogate the cultural appropriation of Indigenous design alongside online source evaluation.